2017
DOI: 10.1016/j.pharep.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anti-diabetic drugs on bone metabolism: Evidence from preclinical and clinical studies

Abstract: Diabetes mellitus is associated with abnormal bone health and an increased risk of fracture even though patients have normal or higher BMD. The mechanisms behind diabetes mellitus- induced various skeletal disorders remain unclear. Anti-diabetic drugs may have negative or positive impact on bone metabolism. For instance, thiazolidinediones increases the bone loss and risk of fracture possibly through PPARγ activation in bone marrow cells and hamper osteoblastogenesis via decreasing Runx2 transcription factor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 152 publications
3
36
0
Order By: Relevance
“…Even in this context, only 1 participant, receiving ertugliflozin 5 mg, met bone rescue criteria. The effects of SGLT2 inhibitors on BMD and fractures have been studied in other members of the class; a 182‐patient study found comparable BMD percentage changes between dapagliflozin 10 mg/day and placebo at 52 weeks; at 102 weeks the difference in LS means (95% CI) at the total hip was −0.45 (−1.32, 0.43) . Canagliflozin treatment resulted in greater percentage reductions in BMD versus placebo at the total hip at all time points in a 104‐week 716‐patient study; at week 104 the difference was −0.9 (−1.5, −0.2) and −1.2 (−1.9, −0.6) for canagliflozin 100 mg and 300 mg versus placebo, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Even in this context, only 1 participant, receiving ertugliflozin 5 mg, met bone rescue criteria. The effects of SGLT2 inhibitors on BMD and fractures have been studied in other members of the class; a 182‐patient study found comparable BMD percentage changes between dapagliflozin 10 mg/day and placebo at 52 weeks; at 102 weeks the difference in LS means (95% CI) at the total hip was −0.45 (−1.32, 0.43) . Canagliflozin treatment resulted in greater percentage reductions in BMD versus placebo at the total hip at all time points in a 104‐week 716‐patient study; at week 104 the difference was −0.9 (−1.5, −0.2) and −1.2 (−1.9, −0.6) for canagliflozin 100 mg and 300 mg versus placebo, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…The AGEs accumulation in collagen triggers apoptosis of the osteoblast cells, whereas abnormal serum levels of markers of bone formation, such as alkaline phosphatase, osteocalcin, insulin‐like growth factor‐1 (IGF‐1), sclerostin, wingless/integrated (Wnt) signaling pathways, and Runt‐related transcription factor 2 (Runx2) levels, suggest abnormal osteoblastogenesis . Similarly, abnormal serum levels of markers of bone resorption, such as receptor activator of NF‐κB ligand, tartrate‐resistant acid phosphatase, and c‐terminal cross‐linked telopeptide, suggest that impaired bone reabsorption may also be involved in the pathogenesis of skeletal fragility in diabetes . Chronic hyperglycemia and AGEs accumulation also contribute to inflammation, a pathophysiological hallmark of diabetes.…”
Section: Sglt2i Effects On Bone Health and Mineral Metabolismmentioning
confidence: 99%
“…(36,38) The increased risk of fracture in these patients may be caused by poor bone quality, possibly because of greater cortical bone porosity and abnormal bone mineral strength. (39) Poor bone quality and abnormal bone microarchitecture in DBD is likely the consequence of many common variables, including chronic hyperglycemia, tissue-specific accumulation of advanced glycation end-products (AGEs), abnormal insulin levels, and chronic low-grade inflammation. (35,36) All these factors may be responsible for bone-remodeling abnormalities in diabetes.…”
Section: Diabetic Bone Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…11,173 Both rosiglitazone and pioglitazone were associated with increased risk of fluid retention and congestive heart failure, 176 leading to certain restrictions on prescribing by the FDA. 11,173 PPARγ has been implicated in bone metabolism, with specific effects on osteoblasts, osteocytes, and osteoclasts 177,178 ; therefore, it is not surprising that TZDs have also been associated with an increased risk of bone fractures based on a plethora of preclinical and clinical studies, 41, [179][180][181][182][183][184][185] although some have suggested that the fracture risk could be similar to the risk in patients with T2D receiving insulin treatment. 186…”
Section: Mechanism Of Actionmentioning
confidence: 99%